CHARACTERISTICS OF THE STRUCTURAL COMPONENTS OF THE MUCOSA AND CARTILAGE OF THE LARYNX OF RATS IN NORMAL (World Science, 2021)
The aim was to conduct a fundamental study of the issue concerning the morphological organization of the mucous membrane and cartilaginous corset of the rat larynx in the norm. Our goal is achieved through the use of morphological methods of preparation and microstructural research.This information in the future will allow to form a morphological base, which will be used to compare the components of the mucous membrane and cartilage of the larynx in the norm with the dynamics of their changes as a result of experimental opioid exposure.